1989
DOI: 10.1159/000111883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Epidermal Growth Factor on the Maturation of Fetal Rat Brain Cells in Aggregate Culture

Abstract: Maturation of astrocytes, neurons, and oligodendrocytes was studied in serum-free aggregating cell cultures of fetal rat telencephalon by an immunocytochemical approach. Cell type-specific immunofluorescence staining was examined by using antibodies directed against glial fibrillary acidic protein (GFAP) and vimentin, two astroglial markers; neuron-specific enolase (NSE) and neurofilament (NF), two neuronal markers, and galactocerebroside (GC), an oligodendroglial marker. It was found that the cellular maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…EGF increases GFAP synthesis in fetal rat brain cells (Laping et al, 1994;Monnet-Tschudi and Honegger, 1989) although this has not been confirmed in cultured mouse astrocytes (Lazarini et al, 1994).…”
Section: Gfap and Nf-äb Regulationmentioning
confidence: 99%
“…EGF increases GFAP synthesis in fetal rat brain cells (Laping et al, 1994;Monnet-Tschudi and Honegger, 1989) although this has not been confirmed in cultured mouse astrocytes (Lazarini et al, 1994).…”
Section: Gfap and Nf-äb Regulationmentioning
confidence: 99%
“…In such studies, the production of floating cell aggregates known as neurospheres (Nph) significantly increases cell yields. Such cultures were initially developed as aggregating cultures in which neural precursor development could be analyzed, studying cell/cell interactions and growth factor requirements (Matthieu et al, 1978, Monnet-Tschudi and Honegger, 1989). Neural precursors can be maintained long-term in vitro as floating Nphs.…”
Section: Introductionmentioning
confidence: 99%
“…Neural precursors can be maintained long-term in vitro as floating Nphs. Nphs have been shown to proliferate efficiently in the presence of epidermal growth factor (EGF) or basic fibroblast growth factor (bFGF), maintaining their multipotentiality (Monnet-Tschudi and Honegger, 1989; Akesson, et al, 2007; Dictus, et al, 2007). In general, after plating, Nphs produce predominantly astrocytes, along with some oligodendrocyte and neuron progenitors (reviewed in Bazan, et al, 2004; Campos, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4) [ 12,[13][14][15], whereas in monolayer cultures, these factors have been shown rather to stimulate astrocyte proliferation [for review see ref. 15], However, in confluent monolayer cultures of hypothala mic astrocytes, bFGF also caused a differentiation of the astrocytes, accompanied by an increase in G F A P and an increase in tenascin [33], These differences in responsive ness could be due to the facilitated cell-cell interactions in the confluent astrocyte cultures and in the 3-dimen sional, histotypic culture model.…”
Section: Discussionmentioning
confidence: 99%
“…This culture system has been shown to be capable of morphogenetic cell-cell interactions [9][10][11], and promotes cell differentiation over cell prolifera tion, especially in response to peptide growth factors such as epidermal growth factor (EGF) [12][13][14], fibro blast growth factor (FGF), and platelet-derived growth factor (PDGF) [15].…”
Section: Introductionmentioning
confidence: 99%